Identification of Akt Association and Oligomerization Domains of the Akt Kinase Coactivator TCL1 - Künstle, Gerald (American Society for Microbiology, 2002)
Serine/threonine kinase Akt/protein kinase B, the cellular homologue of the transforming viral oncogene v-Akt, plays a central role in the regulation of cell survival and proliferation. We have previously demonstrated that the proto-oncogene TCL1 is an Akt kinase coactivator. TCL1 binds to Akt and mediates the formation of oligomeric TCL1-Akt high-molecular-weight protein complexes in vivo. Within these protein complexes, Akt is preferentially phosphorylated and activated. The MTCP1/TCL1/TCL1b oncogene activation is the hallmark of human T-cell prolymphocytic leukemia (T-PLL), a form of adult leukemia. In the present study, using a PCR-generated random TCL1 library combined with a yeast two-hybrid screening detecting loss of interaction, we identified D16 and I74 as amino acid residues mediating the association of TCL1 with Akt. Based on molecular modeling, we determined that the βC-sheet of TCL1 is essential for TCL1 homodimerization. Studies with mammalian overexpression systems demonstrated that both Akt association and oligomerization domains of TCL1 are distinct functional domains. In vitro kinase assays and overexpression experiments in mammalian cells demonstrated that both TCL1-Akt interaction and oligomerization of TCL1 were required for TCL1-induced Akt activation and substrate phosphorylation. Assays for mitochondrial permeability transition, nuclear translocation, and cell recovery demonstrated that both Akt association and homodimerization of TCL1 are similarly needed for the full function of TCL1 as an Akt kinase coactivator in vivo. The results demonstrate the structural basis of TCL1-induced activation of Akt, which causes human T-PLL.